2019
DOI: 10.1073/pnas.1906484116
|View full text |Cite
|
Sign up to set email alerts
|

Wnt activator FOXB2 drives the neuroendocrine differentiation of prostate cancer

Abstract: The Wnt signaling pathway is of paramount importance for development and disease. However, the tissue-specific regulation of Wnt pathway activity remains incompletely understood. Here we identify FOXB2, an uncharacterized forkhead box family transcription factor, as a potent activator of Wnt signaling in normal and cancer cells. Mechanistically, FOXB2 induces multiple Wnt ligands, including WNT7B, which increases TCF/LEF-dependent transcription without activating Wnt coreceptor LRP6 or β-catenin. Proximity lig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 42 publications
(68 reference statements)
5
52
1
Order By: Relevance
“…Validation by RT-qPCR analyses demonstrated that whereas it is not expressed in the parental LNCaP bulk cell population, FAM184A is highly up-regulated in the clones obtained after transfection with the empty expression vector ( Figure 12A). A similar "spontaneous" neuroendocrine transdifferentiation of LNCaP has been described in a study addressing the role of the Wnt activator FOXB2 after stable transfection in LNCaP of a control empty pcDNA3 vector followed by G418 selection [5]. In close agreement with the RNA-Seq data, overexpression of hPCL3S in LNCaP clone 12 strongly repressed the expression of FAM184A and even to a very low level as compared to non-transfected LNCaP cells ( Figure 12A).…”
Section: Effects Of Hpcl3s Overexpression In Lncap and Validation Of supporting
confidence: 84%
See 1 more Smart Citation
“…Validation by RT-qPCR analyses demonstrated that whereas it is not expressed in the parental LNCaP bulk cell population, FAM184A is highly up-regulated in the clones obtained after transfection with the empty expression vector ( Figure 12A). A similar "spontaneous" neuroendocrine transdifferentiation of LNCaP has been described in a study addressing the role of the Wnt activator FOXB2 after stable transfection in LNCaP of a control empty pcDNA3 vector followed by G418 selection [5]. In close agreement with the RNA-Seq data, overexpression of hPCL3S in LNCaP clone 12 strongly repressed the expression of FAM184A and even to a very low level as compared to non-transfected LNCaP cells ( Figure 12A).…”
Section: Effects Of Hpcl3s Overexpression In Lncap and Validation Of supporting
confidence: 84%
“…Two of most commonly used prostate cancer cell lines LNCaP and PC3 are representative of prostatic adenocarcinoma and of Small Cell Neuroendocrine Carcinomas, respectively [3]. Neuroendocrine transdifferentiation of LNCaP cells can be achieved through the ectopic expression of component of the Wnt signaling pathway [4,5] or activation of STAT3 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of WNT7B and its co-receptors are largely restricted to specific tissues, especially the developing brain, where they contribute to blood–brain barrier formation and maintenance through activation of Wnt/β-catenin signaling [ 11 , 12 ]. Increased expression of WNT7B and subsequent Wnt pathway activation have been observed in several cancers, including prostate cancer [ 13 ], pancreatic cancer [ 14 ], and breast cancer [ 15 ]. Nevertheless, as is the case with most Wnt ligands, it remains largely unresolved how WNT7b expression is regulated as well as its underlying mechanisms in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, data regarding upstream regulation of the Wnt signaling pathway is limited. A recent study from Moparthi et al found that FOXB2, an uncharacterized protein, is a potent regulator of Wnt ligand expression and TCF signaling that drives the neuroendocrine differentiation of prostate cancer cells [13]. Another study also reported that MM-1 competitively binds the wnt4 gene promotor region, thereby downregulating promoter activity of wnt4 gene expression [27].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of WNT7B and its co-receptors are largely restricted to speci c tissues, especially the developing brain, where they contribute to blood-brain barrier formation and maintenance through activation of Wnt/β-catenin signaling [11,12]. Increased expression of WNT7B and subsequent Wnt pathway activation have been observed in several cancers, including prostate cancer [13], pancreatic cancer [14], and breast cancer [15]. Nevertheless, as is the case with most Wnt ligands, it remains largely unresolved how WNT7b expression is regulated as well as its underlying mechanisms in CRC.…”
Section: Introductionmentioning
confidence: 99%